Hcp1-loaded staphylococcal membrane vesicle vaccine protects against acute melioidosis - Zhu, Keting; Li, Gang; Li, Jia; Zheng, Mingxia; Peng, Xiaohui; Rao, Yifan; Li, Ming; Zhou, Renjie; Rao, Xiancai (Frontiers in Immunology, 2022)
Burkholderia pseudomallei is the causal agent of melioidosis, a deadly tropical infectious disease that lacks a vaccine. On the basis of the attenuated Staphylococcus aureus RN4220-Δagr (RN), we engineered the RN4220-Δagr/pdhB-hcp1 strain (RN-Hcp1) to generate B. pseudomallei hemolysin-coregulated protein 1 (Hcp1)-loaded membrane vesicles (hcp1MVs). The immunization of BALB/c mice with hcp1MVs mixed with adjuvant by a three-dose regimen increased the serum specific IgG production. The serum levels of inflammatory factors, including TNFα and IL-6, in hcp1MV-vaccinated mice were comparable with those in PBS-challenged mice. The partial adjuvant effect of staphylococcal MVs was observed with the elevation of specific antibody titer in hcp1MV-vaccinated mice relative to those that received the recombinant Hcp1 protein (rHcp1) or MVs derived from RN strain (ΔagrMVs). The hcp1MVs/adjuvant vaccine protected 70% of mice from lethal B. pseudomallei challenge. Immunization with hcp1MVs only protected 60% of mice, whereas vaccination with rHcp1 or ΔagrMVs conferred no protection. Moreover, mice that received hcp1MVs/adjuvant and hcp1MVs immunization had low serum TNF-α and IL-6 levels and no inflammatory infiltration in comparison with other groups. In addition, all surviving mice in hcp1MVs/adjuvant and hcp1MVs groups exhibited no culturable bacteria in their lungs, livers, and spleens five days postinfection. Overall, our data highlighted a new strategy for developing B. pseudomallei vaccine and showed that Hcp1-incorporated staphylococcal MV is a promising candidate for the prevention of acute melioidosis.